Analisis strategi Pemasaran Produk Pembiayaan Multi Guna Aparatur Sipil Negara pada Masa Pandemi Covid-19 di PT Bank Sumut Kantor Cabang Pembantu Syariah Simpang Kayu Besar - Amanda Balqis; Muhammad Latief Ilhamy Nasution (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2022)
Covid-19 pandemic has spread to various countries, including Indonesia. As a result, almost all sectors experienced contractions, including Islamic banking. Covid-19 has had significant impact on world economic development. The covid-19 pandemic is a challenge for business world, including the banking financial services industry. However, Islamic banking is considered quite capable of surviving the storm of impact based on the previous crises' empirical facts. The purpose of this study is to analyze marketing strategy that can be done during the Covid-19 pandemic. The data analysis technique uses descriptive qualitative. The results of the study explained that the post Covid-19 business management strategy for Islamic banking can provide improvement and development of good business sustainability by implementing management strengthening in the fields of marketing, human resources, finance and operations as strategic steps to create an efficient and effective business existence. The conclusion of this study is that Islamic banking are required to have good knowledge management to improve business performance.